2020
DOI: 10.1177/2048872620974612
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic role of plasma galectin-3 levels in acute coronary syndrome

Abstract: Aim: Cystatin C, neutrophil gelatinase-associated lipocalin and galectin-3 have emerged as biomarker candidates to predict cardiovascular outcomes and mortality in the general population as well as in patients with coronary artery or renal disease. However, their predictive role and clinical utility in patients with acute coronary syndromes alone or in combination beyond currently used risk scores remains to be determined. Methods and results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Elevated Gal-3 expression has a strong correlation with the onset and progression of CV disorders, making it closely linked to the adverse remodeling of the heart and MACEs [ 34 ]. MACE remains the leading cause of morbidity and mortality in patients with AMI, and several studies suggest that Gal-3 plays a significant role in predicting adverse events post-AMI [ 34 , 35 , 36 , 37 , 38 , 39 ]. According to research by Grandin E. and colleagues, patients with elevated levels of both BNP and Gal-3 have the highest likelihood of developing HF, suggesting that Gal-3 may provide additional value in assessing HF risk after acute coronary syndrome (ACS) [ 40 ].…”
Section: Inflammatory Factorsmentioning
confidence: 99%
“…Elevated Gal-3 expression has a strong correlation with the onset and progression of CV disorders, making it closely linked to the adverse remodeling of the heart and MACEs [ 34 ]. MACE remains the leading cause of morbidity and mortality in patients with AMI, and several studies suggest that Gal-3 plays a significant role in predicting adverse events post-AMI [ 34 , 35 , 36 , 37 , 38 , 39 ]. According to research by Grandin E. and colleagues, patients with elevated levels of both BNP and Gal-3 have the highest likelihood of developing HF, suggesting that Gal-3 may provide additional value in assessing HF risk after acute coronary syndrome (ACS) [ 40 ].…”
Section: Inflammatory Factorsmentioning
confidence: 99%
“…To account for this, four of the 11 studies (36%) excluded patients with severe renal impairment as indicated by chronic renal disease, serum creatinine > 1.4 mg/dL, and/or requirement for haemodialysis [44,[47][48][49]. Though comparable exclusion criteria were not described in the remaining seven NGAL studies, five studies reported levels of serum creatinine (range 0.81-1.37 mg/dL) and eGFR (median range 65-117 mL/min/1.73 m 2 ) within normal ranges [35,40,[50][51][52], and only a small proportion of patients were reported as requiring dialysis in three studies (range 0.3-2.0%) [35,50,53]. In contrast, Barbarash et al did not state whether the moderate proportion of patients in this study (29%) with marked renal impairment (eGFR < 60 mL/min/1.73 m 2 ) were accounted for in the analysis [54].…”
Section: Association Of Neutrophil-enriched Biomarkers and Cardiovasc...mentioning
confidence: 99%
“…Of the 11 studies investigating circulating NGAL levels, risk ratio data from 7 studies (64%) was extracted and pooled in a random effects model [44,[48][49][50][51][52][53]. Within these studies, a total of 1384 MACE events were recorded for 5488 patients with ACS.…”
Section: Meta-analysis Of Ngalmentioning
confidence: 99%
See 1 more Smart Citation
“…Obeid et al 2 reported that galectin-3 was an independent predictor of both major adverse cardiac and cerebrovascular events and death in patients with acute coronary syndrome. Similarly, Lorenzo-Almorós et al 3 showed that the galectin-3 is associated with increased risk of cardiovascular events in diabetic patients with stable coronary artery disease (CAD).…”
mentioning
confidence: 99%